2019
DOI: 10.1177/1077546319880376
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of stability prediction for high-speed robotic milling of aluminum

Abstract: It has been fully demonstrated that the regenerative chatter theory is applicable for predicting chatter-free milling parameters for computer numerical control machine tools, but researchers are still arguing whether it is effective for robotic milling processes. The main reason is that the robot’s modes greatly shift, depending on its varying dynamic parameters and joint configurations. More experimental investigations are required to study and better understand the mechanism of vibration in robotic machining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This fact underlines that the AVC needs an accurate identification of the disturbance frequency to guarantee the disturbance compensation.The AVC system shows the reduction of vibrations in the middle–high-frequency range. In particular, the FFT analysis (Figure 11) states a vibration peak at 308 Hz that is presumably generated by the chatter phenomenon (Ford et al, 2014; Hao et al, 2020). It is demonstrated that this disturbance influences the workpiece quality surface and accuracy and produces harsh noise and accelerate tool wear.…”
Section: Experimental Tests and Results In Mimo Configurationmentioning
confidence: 99%
“…This fact underlines that the AVC needs an accurate identification of the disturbance frequency to guarantee the disturbance compensation.The AVC system shows the reduction of vibrations in the middle–high-frequency range. In particular, the FFT analysis (Figure 11) states a vibration peak at 308 Hz that is presumably generated by the chatter phenomenon (Ford et al, 2014; Hao et al, 2020). It is demonstrated that this disturbance influences the workpiece quality surface and accuracy and produces harsh noise and accelerate tool wear.…”
Section: Experimental Tests and Results In Mimo Configurationmentioning
confidence: 99%
“…Substitute the harmonic solution ( ) : ( ) (10) 4.1.3 The limit cutting depth of the regenerative chatter…”
Section: Regenerative Chatter Dynamic Modelmentioning
confidence: 99%
“…However, some researchers [10][11][12] found through experimental research that regenerative chatter is the main reason for the instability of robot high-speed milling process. Chatter will not only affect the machining quality, reduce the tool life, and even damage the robot.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al conducted an experimental study of stability prediction for high-speed robotic milling of aluminum. Modal tests were conducted on a milling robot by using a laser tracker and a displacement sensor [ 15 ]. Yin et al studied the machining error prediction and compensation technology for a stone-carving robotic manipulator.…”
Section: Introductionmentioning
confidence: 99%